2021
DOI: 10.7717/peerj.11879
|View full text |Cite
|
Sign up to set email alerts
|

Sponges of Western Mediterranean seamounts: new genera, new species and new records

Abstract: Background The seamounts Ses Olives (SO), Ausias March (AM) and Emile Baudot (EB) at the Mallorca Channel (Balearic Islands, western Mediterranean), are poorly explored areas containing rich and singular sponge communities. Previous works have shown a large heterogeneity of habitats, including rhodolith beds, rocky, gravel and sandy bottoms and steeped slopes. This diversity of habitats provides a great opportunity for improving the knowledge of the sponges from Mediterranean seamounts. Methods Sponges were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 101 publications
1
6
0
Order By: Relevance
“…Our results agree with Galil and Zibrowius (1998) [104] who suggested that Mediterranean seamounts can be considered as isolated refuges for relict populations of species that have disappeared from a previously larger distribution range [70] and that also provide an excellent habitat for rich communities of filter-feeding animals such as sponges [69]. This fact, together with the presence of species and habitats of special interest for their protection, justify the inclusion of the seamounts of the Mallorca Channel within the Natura 2000 network.…”
Section: Ecological Value Of Mallorca Channel Seamountssupporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with Galil and Zibrowius (1998) [104] who suggested that Mediterranean seamounts can be considered as isolated refuges for relict populations of species that have disappeared from a previously larger distribution range [70] and that also provide an excellent habitat for rich communities of filter-feeding animals such as sponges [69]. This fact, together with the presence of species and habitats of special interest for their protection, justify the inclusion of the seamounts of the Mallorca Channel within the Natura 2000 network.…”
Section: Ecological Value Of Mallorca Channel Seamountssupporting
confidence: 92%
“…Some of the identified species up to date have been new to science and new records in the study area or even in the Mediterranean. This is the case of the discovery of the new genus of sponge Foraminospongia, whose type species F. balearica is one of the most abundant sponges at the AM and EB summits and the other two new sponge species F. minuta and Paratimea masuttii [69]. Moreover, new geographical records have been published for another 16 sponges [69] and one ophiuroid [70], with this last species also abundant in the study area.…”
Section: Biodiversity Communities and Habitatsmentioning
confidence: 82%
See 1 more Smart Citation
“…recent surveys carried out in the Mallorca Channel seamounts, including Ausias March, Ses Olives and Emile Baudot seamounts (Massutí et al 2022), have substantially improved our knowledge of Mediterranean invertebrates. This improvement has been particularly important for sponges, with the description, so far, of seven new species (Díaz et al 2021;2023a), but also echinoderms, with the report of the first Mediterranean record of a brittle star of the family Ophiohelidae Perrier, 1873, Ophiomyces grandis lyman, 1879, which showed high abundances in these seamounts despite its absence from insular coasts (Ordines et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have already highlighted the ecological importance of these seamounts, where up to 547 taxa and 29 categories of benthic habitats have been found [14]. Biodiversity studies on unexplored areas, such as seamounts, lead, in most cases, to the discovery of new species for science [15], to new species records [16] or to an increase in species distribution knowledge (geographical and/or bathymetric) [17].…”
Section: Introductionmentioning
confidence: 99%